A user-friendly method for constructing realistic dental model based on two-dimensional/three-dimensional registration. Issue 2 (12th August 2020) - Ke, Yongzhen; Zhao, Wenjie; Yang, Shuai; Wang, Kai; Liu, Jiaying
Abstract : Purpose: This paper aims to obtain a texture dental model with real images and improve the rendering effect of the dental model. Design/methodology/approach: The paper proposes a semiautomatic method to construct a realistic dental model with real images based on two-dimensional/three-dimensional (2D/3D) registration. First, a 3D digital dental model and three intraoral images are obtained by a 3D scanner and digital single-lens reflex camera. Second, the camera projection poses for every intraoral images are calculated by using the single-objective optimization algorithm. Third, with camera poses, the preliminary projection texture mapping is performed; besides, the seam between two textures is marked. Finally, the marked regions are fused based on the image pyramid to eliminate obvious seams. Findings: The paper provides a method to construct a realistic dental model. The method can map three intraoral images to the dental model. The experimental results show that the textured dental model without obvious distortion, dislocation and seams is constructed with simple interactions. Originality/value: The proposed method can be applied to the digital smile design system to improve the communication efficiency between doctors, patients and technicians.